Gundelia tournefortii L. (Kenger): Determination of in vitro Antidiabetic Activities: An edible wild natural food: Gundelia tournefortii L. (Kenger) - Keskin, Merve; Kaya, Gulsen; Keskin, Saban (Progress in Nutrition, 2022)
Diabetes mellitus is a chronic disease that negatively effects daily life. Synthetic drugs, which are inhibitors of α-glucosidase enzymes, are used in its treatment. These drugs may have reaction on organs such as the liver. Therefore, it is important to include plants that inhibit these enzymes in the diet in the treatment of Diabetes mellitus. Gundelia tournefortii L. (Kenger) is an edible wild natural food that is widely used as traditional food. In this study, the biochemical characterization of the Gundelia tournefortii L. (Kenger) extracts were performed and the inhibition effects on α-amylase and α-glycosidase enzymes were investigated. Total phenolic content, antioxidant activity and chemical composition of Gundelia tourneforti L. extracts were determined. The chemical composition of extracts were determined GC/MS. IC50 values of α-amylase and α-glucosidase enzymes of the Gundelia tournefortii L. ethanolic and water extracts were determined as 4.18 ± 0.08 mg/mL and 5.17 ± 0.9 mg/mL, respectively. The results showed that Gundelia tournefortii L. could be used as a supplementary food in the treatment of Type 2 diabetes.